2021
DOI: 10.7717/peerj.10950
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetically-controlled correlates of primate blinking behaviour

Abstract: Eye blinking is an essential maintenance behaviour for many terrestrial animals, but is also a risky behaviour as the animal is unable to scan the environment and detect hazards while its eyes are temporarily closed. It is therefore likely that the length of time that the eyes are closed and the length of the gap between blinks for a species may reflect aspects of the ecology of that species, such as its social or physical environment. An earlier published study conducted a comparative study linking blinking b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Although we conducted our sampling in the field, this could be done using video footage. Being able to analyze video footage means that information about blink duration can also be collected, and previous studies have demonstrated that this additional metric can also vary between individuals and species (Beauchamp, 2017; Matsumoto‐Oda et al, 2018; Rands, 2021; Tada et al, 2013; Yorzinski, 2020a; Yorzinski & Argubright, 2019), and may increase in relation to group size (Beauchamp, 2017). From a field observation perspective, being able to zoom in on detail may also be extremely useful if the observed individuals are a long distance away (as we acknowledge we were lucky with being able to get within 100 m of our sample animals).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we conducted our sampling in the field, this could be done using video footage. Being able to analyze video footage means that information about blink duration can also be collected, and previous studies have demonstrated that this additional metric can also vary between individuals and species (Beauchamp, 2017; Matsumoto‐Oda et al, 2018; Rands, 2021; Tada et al, 2013; Yorzinski, 2020a; Yorzinski & Argubright, 2019), and may increase in relation to group size (Beauchamp, 2017). From a field observation perspective, being able to zoom in on detail may also be extremely useful if the observed individuals are a long distance away (as we acknowledge we were lucky with being able to get within 100 m of our sample animals).…”
Section: Discussionmentioning
confidence: 99%
“…Blinking (the temporary closure of both eyes, involving movements of the eyelids: Blount, 1927) is a good example of an activity where an individual is momentarily unable to visually scan the environment. It is an essential maintenance behavior to keep the eyes moist and clean (Ranti et al, 2020) and is conducted tens of times every minute in some species of diurnal mammals (Rands, 2021; Stevens & Livermore, 1978; Tada et al, 2013) and birds (Kirsten & Kirsten, 1983). Although a blink takes only a fraction of a second, the sum of this loss of visual information over multiple blinks could be substantial for the individual.…”
Section: Introductionmentioning
confidence: 99%
“…The current study therefore uses video footage of individual behaviour, which should provide accurate, unbiased data. Previous studies in other species [20,[22][23][24][25][26] have shown that video analysis is an accurate means of collecting this information. We would expect that as group size varies, both deer species should modify their blink rate, duration, and length of time between blinks -individuals in a larger group would be expected to be less vigilant, therefore blinking more frequently and for longer durations with shorter inter-blink intervals, as predicted by the group vigilance and risk allocation hypotheses [5,10,27].…”
Section: Introductionmentioning
confidence: 99%
“…Blinking has been studied in humans, showing that individuals will blink less often when faced with a cognitively demanding task [19] or when watching content that is perceived to be important [18]. These same principles can be applied to vigilance in other species, whereby an individual may supress blinking behaviour when group size is smaller due to the increase in vigilance demand [20]. This suppression may occur as a reduction in blink duration, or an increase in the interval between blinks so that the blink rate is reduced [21,22].…”
Section: Introductionmentioning
confidence: 99%